Pengaruh Social Media Influencer, Kepercayaan dan Perilaku Konsumen Terhadap Keputusan Pembelian Di Shoope: Studi Kasus Pada Generasi Z Mahasiswa Kota Malang - Asyadi, Erda Dwi Ananda; Alrasyid, Harun; Wahyuningtyas, Nanik (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to determine the influence of Social Media Influencers, Trust, and Consumer Behavior on Purchasing Decisions at Shopee, focusing on generation Z students in Malang City. The research method used is quantitative with a survey approach by distributing questionnaires to 124 respondents selected purposively. Data analysis was carried out using multiple linear regression with the help of SPSS. The results of the study indicate that social media influencers, trust, and consumer behavior have a positive and significant effect on purchasing decisions. Keywords: Social Media Influencer, Trust, Consumer Behaviour, Purchasing Decisions